The Everafter War / 7. - Buckley, Michael, 1969- (Buckley, Michael, 1969- Sisters Grimm, 2010)
After their parents awake from a sleeping spell, Daphne and Sabrina become caught in the middle of a war between the Scarlet Hand and Prince Charming's Everafter army and learn a shocking secret about a deadly enemy.